The Management of Healthy Cafeteria on Students’ Academic Achievement - Silvia Agustin; Putri Indah Pertiwi; Husen Windayana (Indonesian Journal of Multidisciplinary Science, 2022)
Children's health must be supported and maintained in the family environment and school environment. Making a healthy canteen there must be planning in advance, with careful planning will facilitate activity. Organizing is planned to determine whose duties and authorities will carry out a particular task to achieve a common goal. The implementation of this healthy canteen must go well, this healthy canteen will provide good benefits not only to its students but to the people who are in the canteen environment. This healthy canteen must also be supervised by relevant parties such as local health centers. With a healthy canteen, student food can be echoed and then the student's health is maintained and will result in increased student learning achievement.